Vulnerabilities, victimisation, romance and indulgence: Thai women's pathways to prison in Cambodia for international cross border drug trafficking - Jeffries, Samantha (International journal of law, crime and justice, 2019)
There is an extensive body of western research exploring women's pathways to prison. These studies show that the lives of convicted women are typically characterised by extensive childhood and/or adulthood victimisation, mental ill health, men's influence/control and economic marginalisation. Non-western feminist pathways research is nevertheless sparse as are studies on women imprisoned for drug trafficking. Using life history interviews with Thai foreign national women imprisoned in Cambodia for international cross-border drug trafficking, this paper explores the circumstances and criminal justice experiences propelling them into prison. Results reveal four distinct pathways to prison: 1) the criminogenic pathway, 2) the romantic susceptibility pathway, 3) the domestic violence pathway, 4) the self-indulgent pathway.